Unravelling the Non-Native Low-Spin State of the Cytochrome c-Cardiolipin Complex: Evidence of the Formation of a His-Ligated Species Only - Milazzo, Lisa; Tognaccini, Lorenzo; Howes, Barry D; Sinibaldi, Federica; Piro, Maria C; Fittipaldi, Maria; Baratto, Maria C; Pogni, Rebecca; Santucci, Roberto; Smulevich, Giulietta (Biochemistry (Easton), 2017)
The interaction between cytochrome c (Cyt c) and cardiolipin (CL) plays a vital role in the early stages of apoptosis. The binding of CL to Cyt c induces a considerable increase in its peroxidase activity that has been attributed to the partial unfolding of the protein, dissociation of the Met80 axial ligand, and formation of non-native conformers. Although the interaction between Cyt c and CL has been extensively studied, there is still no consensus regarding the conformational rearrangements of Cyt c that follow the protein-lipid interaction. To rationalize the different results and gain better insight into the Cyt c-CL interaction, we have studied the formation of the CL complex of the horse heart wild-type protein and selected mutants in which residues considered to play a key role in the interaction with CL (His26, His33, Lys72, Lys73, and Lys79) have been mutated. The analysis was conducted at both room temperature and low temperatures via ultraviolet-visible absorption, resonance Raman, and electron paramagnetic resonance spectroscopies. The trigger and the sequence of CL-induced structural variations are discussed in terms of disruption of the His26-Pro44 hydrogen bond. We unequivocally identify the sixth ligand in the partially unfolded, non-native low-spin state that Cyt c can adopt following the protein-lipid interaction, as a His ligation, ruling out the previously proposed involvement of a Lys residue or an OH ion.